HUBUNGAN PSYCHOLOGICAL WELL BEING DENGAN KINERJA KADER KESEHATAN JIWA - Yunita, Rizka; Isnawati, Iin Aini (STIKes Maharani Malang, 2019)
Introduction: Patients with mental disorders every year has increased in number. People with mental disorders often become a burden, especially for families and communities so it needs immediate treatment. One of them is by encouraging the active role of the community through the empowerment of mental health cadres as the closest elements of the community. Cadres in carrying out their duties must first experience a healthy mind and body. The purpose of this study was to analyze psychological well being with the performance of mental health cadres. Method: This study uses analitic corelation research design with cross sectional approach. The population and sample were all mental health cadres in Karangbong Village, Pajarakan District, Probolinggo District totaling 25 people. The sampling technique uses total sampling. Results: Based on the Pearson statistical test results found that the value of ? value of 0.001 which means there is a significant relationship between psychological well being with the performance of mental health cadres. While the correlation value r of 0.621 means that there is a positive and strong correlation. Discussion: It can be concluded that the better the psychological well being, the better the performance of mental health cadres.